2020
DOI: 10.1021/acsomega.0c03318
|View full text |Cite
|
Sign up to set email alerts
|

Z-Scheme LaCoO3/g-C3N4 for Efficient Full-Spectrum Light-Simulated Solar Photocatalytic Hydrogen Generation

Abstract: Photocatalytic decomposition of water is the most attractive method for the sustainable production of hydrogen, but the development of a highly active and low-cost catalyst remains a major challenge. Here, we report the preparation of LaCoO 3 /g-C 3 N 4 nanosheets and the utilization of LaCoO 3 instead of noble metals to improve the photocatalytic activity for the production of hydrogen. First, LaCoO 3 was successfully prepared by the sol−gel method, and then a series of highly efficient Z-scheme LaCoO 3 /g-C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…The latter one is assigned to the sp 2 -bonded carbon in the heterocycle (N–CN) of aromatic g-C 3 N 4 , which is regarded as the major carbon in the structure of the conjugated system . The N 1 s photoelectron signal can be fitted into four peaks, which can be assigned to C–NC (398.1 eV), tertiary nitrogen N–(C)­3 groups (399.8 eV), amino functional C–N–H groups (401.9 eV), and π-excitation (404.6 eV), respectively . All the peaks of C 1s and N 1s consist well with those reported of pristine g-C 3 N 4 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The latter one is assigned to the sp 2 -bonded carbon in the heterocycle (N–CN) of aromatic g-C 3 N 4 , which is regarded as the major carbon in the structure of the conjugated system . The N 1 s photoelectron signal can be fitted into four peaks, which can be assigned to C–NC (398.1 eV), tertiary nitrogen N–(C)­3 groups (399.8 eV), amino functional C–N–H groups (401.9 eV), and π-excitation (404.6 eV), respectively . All the peaks of C 1s and N 1s consist well with those reported of pristine g-C 3 N 4 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…A recent report showed that LaCoO 3 /g‐C 3 N 4 demonstrates high performance because of promising characteristics of g‐C 3 N 4 (owing to the pyridinic and pyrrolic N), sp 2 hybridized carbon, high stability, and efficient charge transfer capacity of LaCoO 3 . [ 144 ] The use of LaCoO 3 /g‐C 3 N 4 photocatalyst reduced the electrons/holes recombination and increased the catalytic activity. The interconnected junction and high bonding strength between g‐C 3 N 4 nanosheets and LaCoO 3 NPs produced H 2 at a high rate, that is, 1046.15 μmolh −1 g −1 , and this rate of H 2 production is many times higher than the individual substrates.…”
Section: Experimental Advances In Z‐scheme Water Splittingmentioning
confidence: 99%
“…E 0 stands for free-electron energy on the H 2 scale (4.5 eV vs NHE). The X value of the LaFeO 3 and LaCoO 3 is calculated to be 5.58 eV and 5.64 eV, respectively [67] , [68] with the reference absolute electronegativities values of La, Fe, Co, and O were 3.1, 4.06, 4.3, and 7.54 eV, respectively as mentioned in ‘Pearson Absolute Electronegativity table’. The VB potential value for the LaCo 0.2 Fe 0.8 O 3 sample (E VB = 1.605 eV) was determined to be the lowest in the sequence, with a CB potential of −0.225 eV leading to a narrow bandgap (1.83 eV) that absorbs optimum visible photons.…”
Section: Resultsmentioning
confidence: 94%